A pilot study designing a website to enhance the well being of caregivers of children with cerebral palsy - Boixadós, Mercè; Universitat Oberta de Catalunya (2014)
The objective is to present a website designed to improve the quality of life of caregivers of children with cerebral palsy and show data concerning its usefulness. The website was developed in accordance with scientific literature about caregivers’ burden. We organized the website around different sections (e.g. family communication, learning to relax) and social support forums. The interactive features of the site were designed to accommodate different caregivers’ needs and enable them to choose different pathways according to their own individual needs. Participants were 10 caregivers who took part in a pilot study and completed a questionnaire to analyze the usefulness of the website after five months using it. Preliminary results suggested that the website was useful for participants. The most useful sections were the “peer-to-peer” and the professional forums. This study shows the potential of an online intervention for parents of children with cerebral palsy.